Aplikasi E-Learning Seni Budaya Berbasis Android Menggunakan Teknologi Phonegap Pada SMK Negeri 1 Depok - Sri Melati Sagita; Rini Amalia (Universitas Indraprasta PGRI Jakarta, 2018)
The concept of e-learning brings the impact of the conventional transfer of education into a digital form, both in content and system. SMK N 1 Depok in the learning process is still conventional, where the learning process is done with the condition of meeting between students and teachers in the classroom. The learning process can be hampered if the meeting does not exist. thus hampering the learning process in SMK N 1 Depok which resulted in less understanding of students on a subject. Developing android-based e-learning using phonegap technology is expected to improve the quality of learning and learning outcomes. This e-learning application provides convenience to the users (students) to get the subject matter of Art Culture in the form of theory, pictures and video. In this application there is also a workout problem that can be done by students and the results of their work can be seen directly. This application can provide convenience for its users so no need to bother to bring a book that is relatively ineffective. By simply opening this app on your Android phone, information about Art Culture lesson material can be obtained easily.